Essays on preferential trade liberalisation and domestic tax policy: CGE evaluations for Thailand and for India - Lochindaratn, Pachara (2009)
This thesis employs the CGE approach to appraise three distinctive issues. Using hypothetical data, Essay 1 estimates how customs union outcomes are sensitive to market size and competitiveness. Further, common external tariffs are adjusted to ensure necessarily welfare-improving outcomes, thereby completely eliminating trade diversion. The results confirm that members’ gains are proportional to the union size, and the degree of market competition significantly alters the welfare outcome. Once common external tariffs are endogenised, members gain less while the whole world gains more as non-members become unaffected by trade diversion.